Valoración de la resiliencia empresarial y estrategias de gestión de riesgos ante la crisis económica o desastres naturales en las empresas de la ciudad de Ambato - Padilla Gallegos, Jeampier Alejandro (2024)
In the city of Ambato, there are approximately 429 legally active companies distributed across sectors such as agriculture, commerce, industry, and others. These companies face an economic, natural, and social environment filled with uncertainties and risks. This situation creates the need for businesses to develop risk management strategies and contingency plans that allow them to respond appropriately to potential crises, whether economic or caused by natural disasters. In this context, business resilience plays a key role, as it determines the organization's ability to adapt and recover from adverse situations. However, resilience is not the same for all companies; their level of preparedness and response capacity will depend on the specific characteristics of each company and the sector in which they operate. Nevertheless, many companies in the city of Ambato lack the knowledge and tools necessary to adequately manage risks, leaving them vulnerable to unexpected crises. Although most companies recognize the importance of resilience as a means to cope with adverse situations, recent research results show a significant lack of knowledge regarding risk management strategies. This knowledge gap translates into a reduced capacity to respond to critical events and hinders the implementation of effective recovery plans. Consequently, many companies in the city of Ambato are exposed to considerable economic losses due to their lack of preparedness for economic crises or natural disasters. This highlights the urgent need to implement training and skill development programs in risk management, both for executives and employees. Additionally, it is recommended that companies seek specialized advice to develop adequate and personalized contingency plans that meet the specific needs of each organization. It is important to emphasize that business resilience and risk management are essential to ensure survival and success in an increasingly changing and complex environment. By adopting proactive strategies and strengthening their internal capabilities, companies will not only be able to face present challenges but also turn crises into opportunities for growth and development. Long-term sustainability will depend on their ability to adapt to future challenges.